Analisis Pengendalian Persediaan Raw Material Untuk Meningkatkan Efisiensi Produksi Hand Stand Mixer Pada Pt Blue Gas Indonesia Dengan Metode Material Requirement Planning (MRP) - Puspita, Sesaria Mardhiani Rachma; Sitorus, Purbanuara Parlindungan; Theresia, Noviana Marianti (Jurnal Sistem Transportasi & Logistik, 2024)
PT. Blue Gas Indonesia is a company engaged in sales, distribution, gas refiling and assembling. This company also has a household equipment production and assembly business unit under the Vienta trademark and markets Blue Gas and Vienta kitchen equipment products such as Hand Stand Mixers. This company has a problem, namely PT. Blue Gas Indonesia still uses a manual system to plan Raw materials for making handstand mixers. This can cause problems, such as frequent calculation errors when Raw material stock is too small, resulting in the production process being hampered. Therefore, this research aims to find out the optimal quantity of Raw material needed and to know when to place a new order using the MRP Method, Lot For Lot-for-lot technique, Economic Order Quantity, and Period Order Quantity. The results of the research produced From the results of analysis using the Material Requirement Planning method by calculating Lot Sizing using three techniques, namely Lot For Lot, Economic Order Quantity, and Periodic Order Quantity on Raw materials for Hand Stand Mixer products, it can be concluded that the lotting or lot-sizing technique costs money. The minimum inventory for almost all Raw materials is the Lot For Lot technique with a total inventory cost of IDR 4.422.348.978,59.